2022
DOI: 10.1136/rapm-2022-103482
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon-performed pericapsular nerve group (PENG) block for total hip arthroplasty using the direct anterior approach: a cadaveric study

Abstract: BackgroundDuring total hip arthroplasty (THA) using the direct anterior approach, orthopaedic surgeons can identify all anatomical landmarks required for pericapsular nerve group (PENG) blocks and carry out the latter under direct vision. This cadaveric study investigated the success of surgeon-performed PENG block. Success was defined as dye staining of the articular branches of the femoral and accessory obturator nerves.Methods11 cadavers (18 hip specimens) were included in the current study. To simulate THA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…More importantly, if PENG block does frequently end up as an iliopectineal bursa injection with potential bursal rupture/puncture, the injectate can then manage to breach the medial border of IP (formed by IT and its closely associated iliopectineal bursa) and subsequently spread anteromedially along the surface of PM to catch the femoral nerve proper within FIC, causing quadriceps weakness. In support of our speculation, a recently published surgeon-performed PENG block cadaver study showed that femoral nerve proper and obturator nerve divisions were stained in 5.6% and 11.1% of their specimen, and abundant dye could again be seen spreading along the undersurface of IT (corresponding to iliopectineal bursa) and further extended anteromedially to involve femoral nerve proper and posteromedially to obturator nerves (extrapelvic) [ 39 ].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…More importantly, if PENG block does frequently end up as an iliopectineal bursa injection with potential bursal rupture/puncture, the injectate can then manage to breach the medial border of IP (formed by IT and its closely associated iliopectineal bursa) and subsequently spread anteromedially along the surface of PM to catch the femoral nerve proper within FIC, causing quadriceps weakness. In support of our speculation, a recently published surgeon-performed PENG block cadaver study showed that femoral nerve proper and obturator nerve divisions were stained in 5.6% and 11.1% of their specimen, and abundant dye could again be seen spreading along the undersurface of IT (corresponding to iliopectineal bursa) and further extended anteromedially to involve femoral nerve proper and posteromedially to obturator nerves (extrapelvic) [ 39 ].…”
Section: Discussionsupporting
confidence: 64%
“…Finally, we found 5 cadaveric dye injection studies and 32 clinical studies to be included in our review ( Figure 3 ). Among the cadaveric studies, there are four articles on PENG block [ 22 , 37 , 38 , 39 ] and one on IPB [ 8 ]. All clinical studies except one randomized controlled trial (RCT) [ 7 ] and two recently published case series [ 40 , 41 ] utilized PENG block.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Kitcharanant et al 28 conducted a cadaveric assessment of dye spread pattern after surgeon-performed PENG block for THA using the direct anterior approach. The PENG block was performed by injecting 20 mL of 0.1% methylene blue after inserting a needle lateral to the psoas tendon with direct visualization by the orthopedic surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…26 Some authors have expressed concern high local anesthetic volume may lead to anesthetic spread to the FN, causing inadvertent quadriceps weakness. 20,24,27 Previously, Kitcharanant et al 28 conducted a cadaveric assessment of dye spread pattern after surgeonperformed PENG block with 0.1% of methylene blue for THA using the direct anterior approach. However, to our knowledge, there are only a few cadaveric and radiological studies related to injectate spread during implementation stratified by different volumes and performed by anesthesiologists.…”
mentioning
confidence: 99%